SIMULASI KESIAPAN PERSALINAN MENURUNKAN KECEMASAN IBU TRIMESTER III DI PRAKTEK MANDIRI BIDAN KASIH IBU - Megawati Sinambela; Reysi Tane; Meta Rosaulina (INSTITUT KESEHATAN DELI HUSADA, 2022)
High anxiety faced by mothers in the third trimester when facing the delivery process is a problem that is often faced due to psychological factors that have not received attention from birth attendants. Community service simulating labor readiness reduces maternal anxiety in the third trimester in the independent practice of the midwife of maternal love, in principle reducing the mother's anxiety and fear in facing childbirth so that childbirth will be felt pleasant and the mother has an attitude of readiness in facing childbirth. This activity is in the form of providing education and knowledge about the changes that occur in the third trimester of pregnancy and preparation for childbirth as well as an overview of the process and conditions during labor. The results of this activity from the discussion found that 100% of mothers were aware of the changes that occurred in the third trimester of pregnancy and the stages of labor and some of them already knew how to reduce pain during labor. with a low level of anxiety, which means that mothers in dealing with labor have reduced levels of anxiety or fear.